COVID-19: Transatlantic Declines in Pediatric Emergency Admissions. Issue 11 (November 2020) - Isba, Rachel; Edge, Rhiannon; Auerbach, Marc; Cicero, Mark X.; Jenner, Rachel; Setzer, Erika; Broughton, Emily; Keegan, Thomas
Abstract : Introduction: This cross-sectional study looked at the impact of the SARS-CoV-2/COVID-19 pandemic on pediatric emergency department (PED) attendances and admissions (as a proxy for severity of illness) in the United States and United Kingdom. Methods: Data were extracted for children and adolescents, younger than 16 years, attending Royal Manchester Children's Hospital (RMCH, United Kingdom), and Yale New Haven Children's Hospital (YNHCH, United States). Attendances for weeks 1 to 20 of 2020 and 2019 were compared, and likelihood of admission was assessed via calculation of odds ratios, using week 13 (lockdown) as a cutoff. Results: Attendance numbers for each PED decreased in 2020 compared with 2019 (RMCH, 29.2%; YNHCH, 24.8%). Odds of admission were significantly higher after lockdown than in 2019—RMCH (odds ratio, 1.26; 95% confidence interval, 1.08–1.46) and YNHCH (odds ratio, 1.60; 95% confidence interval, 1.31–1.98). Conclusions: Although the absolute numbers of children and adolescents attending the PED and being admitted decreased after lockdown, the acuity of illness of those attending appears to be higher.